2008
DOI: 10.1097/cej.0b013e328305a0b9
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air pollution from solid fuel use, chronic lung diseases and lung cancer in Harbin, Northeast China

Abstract: In some areas of China, indoor air pollution (IAP) originating principally from the combustion of solid fuels has a relevant role in lung cancer. Most previous studies focused on the female population and only a few on both the sexes. We analyzed the relationship between IAP from solid fuel use and selected chronic lung diseases and lung cancer risk in Harbin, Northeast China, an area with a very high base line risk of lung cancer for both the sexes. We used data from a case-control study conducted between 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 27 publications
3
22
0
1
Order By: Relevance
“…The high incidence of lung cancer among elderly subjects may be related to factors like smoking status, food habit, occupational exposure and infectious diseases [19,22,[23][24][25]. Moreover, the lack of observed gender predisposition for lung cancer types among subjects more than 60 years of age supports ours assumption that the elderly in China are predisposed to malignancy [26] ( Table 3).…”
Section: Discussionsupporting
confidence: 60%
“…The high incidence of lung cancer among elderly subjects may be related to factors like smoking status, food habit, occupational exposure and infectious diseases [19,22,[23][24][25]. Moreover, the lack of observed gender predisposition for lung cancer types among subjects more than 60 years of age supports ours assumption that the elderly in China are predisposed to malignancy [26] ( Table 3).…”
Section: Discussionsupporting
confidence: 60%
“…Here we report that COPD is associated with lung cancer risk, furthering the previous observations and supporting the hypothesis that COPD is not only an independent risk factor for lung cancer, but also that COPD may mediate the coal exposure and lung cancer relationship by serving as an intermediary in the causal pathway. A study carried out in Northeast China also supports this hypothesis[14]. Galeone et al found that history of COPD was associated with about a 4-fold increased risk of lung cancer in Harbin[14].…”
Section: Discussionmentioning
confidence: 81%
“…In 2010, the International Agency for Research on Cancer (IARC) declared that the pollution produced by biomass utilization is considered as a possible carcinogen for human (Reid et al, 2012). In a study reported in China in 2008, an association between the indoor air pollution (IAP) due to solid fuel and chronic respiratory disease and lung cancer was confirmed (Galeone et al, 2008). Also, the association between more efficient ventilation of residential building and reduced risk of respiratory diseases has been investigated in a study (Kurmi et al, 2010).…”
Section: Discussionmentioning
confidence: 93%